Aplikasi Profiling Tes Psikologi Berbasis Website dalam Pendidikan - Andre Julius; Miki Wijana; Alfaiz Alfaiz; Azmatul Khairiyah Sari (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
This research aim to developing new application and program of psychological profiling testing. This based on need assessment about condition of pandemic that needed for psychological test in website based, for facilitate a testee for testing service. This research was a research and development and using Borg & Gall’s design with 9 phase such exploration study, literature review, arrangement of hypothetic, expert judgement, model revision, try out, analysis and revision, final model, diseminasion and socialization. This product using expert judgement and validation process with Interrater Agreement Model, and research subject were guidance and couneling students of Masoem University. The result of the research with the development process have been revised and have succeeded in developing and functioning of the guidance and counseling and profiling psychological test for all testee or student were needed in Masoem University.